A Prunus avium L. Infusion Inhibits Sugar Uptake and Counteracts Oxidative Stress-Induced Stimulation of Glucose Uptake by Intestinal Epithelial (Caco-2) Cells - Juliana A. Barreto-Peixoto; Cláudia Silva; Anabela S. G. Costa; Gerardo Álvarez-Rivera; Alejandro Cifuentes; Elena Ibáñez; M. Beatriz P. P. Oliveira; Rita C. Alves; Fátima Martel; Nelson Andrade (MDPI AG, 2023)
Sweet cherry (Prunus avium L.) is among the most valued fruits due to its organoleptic properties and nutritional worth. Cherry stems are rich in bioactive compounds, known for their anti-inflammatory and antioxidant properties. Innumerable studies have indicated that some bioactive compounds can modulate sugar absorption in the small intestine. In this study, the phenolic profile of a cherry stem infusion was investigated, as well as its capacity to modulate intestinal glucose and fructose transport in Caco-2 cells. Long-term (24 h) exposure to cherry stem infusion (25%, v/v) significantly reduced glucose (3H-DG) and fructose (14C-FRU) apical uptake, reduced the apical-to-basolateral Papp to 3H-DG, and decreased mRNA expression levels of the sugar transporters SGLT1, GLUT2 and GLUT5. Oxidative stress (induced by tert-butyl hydroperoxide) caused an increase in 3H-DG uptake, which was abolished by the cherry stem infusion. These findings suggest that cherry stem infusion can reduce the intestinal absorption of both glucose and fructose by decreasing the gene expression of their membrane transporters. Moreover, this infusion also appears to be able to counteract the stimulatory effect of oxidative stress upon glucose intestinal uptake. Therefore, it can be a potentially useful compound for controlling hyperglycemia, especially in the presence of increased intestinal oxidative stress levels.